A one-component self-drying water-based anticorrosive coating

By using components such as multi-phase self-crosslinked acrylic emulsions and polyurethane dispersions in single-component self-drying water-based paint, the density and cross-linking density of the paint film are improved, and the anti-corrosion and rust function and construction matching are solved. The problem of this problem has achieved significant improvement in salt spray resistance and weather resistance, and is suitable as a bottom-mounted product.

CN116731579BActive Publication Date: 2025-01-14DRAGON BRAND COATINGS (BEIJING) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310669904.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-01-14
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

The existing single-component self-drying water-based paint has poor anti-corrosion and rust function, insufficient salt spray resistance, and poor construction supporting properties. It is difficult to match with two-component water-based polyurethane systems, and it is prone to bottom-biting problems.

Method used

Components such as multiphase self-crosslinked anionic acrylic-styrene copolymer emulsion, polycarbonate polyurethane dispersion, epoxy acrylic acid modified alkyd resin and hexamoxymethyl melamine resin are used to mix them in specific ways Steps and proportions to increase the density and cross-linking density of the paint film, increase weather resistance and adhesion.

Benefits of technology

It significantly improves the salt spray resistance, weather resistance and adhesion of the paint film, and extends the salt spray resistance to 720 hours. It has excellent water resistance in the early stage. It is suitable as a bottom-combination product. It can be used with a variety of topcoat systems to improve Construction and application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004272492020000071
    Figure BDA0004272492020000071
  • Figure BDA0004272492020000081
    Figure BDA0004272492020000081
Patent Text Reader

Abstract

The present application provides a one-component self-drying water-based anticorrosive coating, which comprises, by weight, 30 to 40 parts of water-based acrylic emulsion, 8 to 12 parts of alkyd resin, 4 to 6 parts of water-based polyurethane dispersion, and 4 to 6 parts of amino resin. The present application provides a one-component self-drying water-based anticorrosive paint that can be used as both a bottom and a top, and has excellent weather resistance and anticorrosion and antirust functions. It has low VOC content, high hardness, excellent adhesion, good salt spray resistance, excellent weather resistance, and excellent construction matching (it can be used with a variety of products such as two-component polyurethane topcoat, acrylic topcoat, alkyd topcoat, epoxy topcoat, etc.), and is particularly suitable for use as various bottom-to-top products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to but is not limited to the field of water-based resins and water-based coatings, and in particular to but is not limited to a one-component self-drying water-based anti-corrosion coating. Background Art

[0002] With the popularization of water-based industrial paints, the market's acceptance of water-based paints is getting higher and higher. However, in addition to the general steel structure field, two-component water-based paints are widely used, such as two-component water-based epoxy, two-component water-based polyurethane, etc., especially when paired with a two-component water-based polyurethane system, a two-component water-based epoxy system or solvent-based paint is often used. The main reason for not using a single-component water-based anti-corrosion coating is that its own anti-corrosion and anti-rust function is poor (generally salt spray resistance does not exceed 240h), and it is prone to bite the bottom as a primer. Compared with two-component water-based epoxy, the construction advantages of a single-component self-drying water-based paint are also obvious. There is no problem of the application period after mixing, and the construction is wide. It can be applied in a variety of ways, such as pouring and dipping. Therefore, the development of a single-component self-drying water-based paint with excellent anti-rust and anti-corrosion functions, excellent adhesion on common substrates, and can be used with multiple systems such as a two-component water-based polyurethane system will inevitably be widely recognized by the market. Summary of the invention

[0003] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.

[0004] The present application provides a one-component self-drying water-based anti-corrosion coating, characterized in that the one-component self-drying water-based anti-corrosion coating comprises, by weight: 30 to 40 parts of water-based acrylic emulsion, 8 to 12 parts of alkyd resin, 4 to 6 parts of water-based polyurethane dispersion and 4 to 6 parts of amino resin.

[0005] In one embodiment provided in the present application, the aqueous acrylic emulsion is a multiphase self-crosslinking anionic acrylic acid-styrene copolymer emulsion;

[0006] The aqueous polyurethane dispersion is a polycarbonate polyurethane dispersion;

[0007] The alkyd resin is an epoxy acrylic modified alkyd resin;

[0008] The amino resin is hexamethoxymethyl melamine resin;

[0009] In one embodiment provided in the present application, the one-component self-drying water-based anti-corrosion coating includes, by weight: 30 to 40 parts of water-based acrylic emulsion, 8 to 12 parts of alkyd resin, 4 to 6 parts of water-based polyurethane dispersion, 4 to 6 parts of amino resin, 1.5 to 2 parts of pH adjuster, 5 to 10 parts of deionized water, 2 to 4 parts of cosolvent, 0.3 to 0.5 parts of wetting agent, 0.3 to 0.5 parts of dispersant, 0.2 to 0.3 parts of defoaming agent, 2 to 20 parts of pigment, 10 to 25 parts of filler, 0.5 to 1 parts of anti-flash rust agent and 0.5 to 1 parts of thickener.

[0010] In one embodiment provided in the present application, the pH adjuster is selected from any one or more of dimethylethanolamine, inorganic silanol and 2-amino-2-methyl-1-propanol.

[0011] In one embodiment provided in the present application, the co-solvent is selected from any one or more of dipropylene glycol dimethyl ether DMM, dipropylene glycol methyl ether DPM and propylene glycol methyl ether propionate PMP.

[0012] In one embodiment provided in the present application, the defoaming agent is selected from any one or more of Tego843, BYK011, DF-208 of Shanghai Zhongyi Chemical and Foamex812 of Evonik; optionally, the defoaming agent is a mixture of Tego843 and BYK011 in a weight ratio of 1:3.

[0013] In one embodiment provided in the present application, the dispersant is selected from any one or more of Shanghai Yuanhe Chemical Verapon B110 and Rogers PORON NC, Shanghai Zhongyi Chemical DP-610, Evonik GA-100 and Arkema Coadis 790; optionally, the dispersant is a mixture of Verapon B110 and PORON NC in a weight ratio of 2:1.

[0014] In one embodiment provided in the present application, the wetting agent is selected from any one or more of Surfynol AD01 of Air Chem, Surfynol 104 of Evonik, WA-541B of Shanghai Zhongyi Chemical, and BYK-P104 of BYK Chemical.

[0015] In one embodiment provided in the present application, the thickener is selected from any one or more of Rohm and Haas RM-12W, Hemmings Rheolate 299, Shanghai Zhongyi Chemical's CX-380, Arkema's 53L and Evonik 3010; optionally, the thickener is a mixture of Rohm and Haas RM-12W and Hemmings Rheolate 299 in a weight ratio of 1:1.

[0016] In one embodiment provided in the present application, the anti-flash rust agent is selected from any one or more of Hemmings ED617F, Shanghai Pengpan 142DA, Beijing Zhitu Chemical ZT706 and Shanghai Tianyu Chemical ED-617F; optionally, the anti-flash rust agent is a mixture of Hemmings ED617F and Shanghai Pengpan 142DA in a weight ratio of 1:1.

[0017] In one embodiment provided in the present application, the pigment is selected from titanium dioxide; optionally, the titanium dioxide is selected from Lomon Titanium Dioxide LR-996.

[0018] In one embodiment provided in the present application, the filler is selected from any one or more of barium sulfate, talc and aluminum tripolyphosphate.

[0019] In one embodiment provided in the present application, the barium sulfate is precipitated barium sulfate passing through a 1500 mesh sieve, and the talc is talc passing through a 1500 mesh sieve.

[0020] In one embodiment provided in the present application, the filler is a mixture of barium sulfate, talc and aluminum tripolyphosphate in a weight ratio of 1:1:1.

[0021] In one embodiment provided in the present application, the pH value of the one-component self-drying water-based anti-corrosion coating is 8 to 10.

[0022] On the other hand, the present application provides a method for preparing the above-mentioned one-component self-drying water-based anti-corrosion paint, comprising the following steps:

[0023] The alkyd resin, the cosolvent and the pH adjuster are uniformly mixed, which is referred to as Mixing 1 to obtain Mixing 1;

[0024] The mixture 1 and the amino resin are uniformly mixed, which is referred to as mixture 2, to obtain mixture 2;

[0025] Mixing the mixture 2 and the deionized water uniformly, recorded as mixture 3, to obtain mixture 3;

[0026] The mixture 3 is uniformly mixed with the dispersant and the defoamer, which is recorded as mixture 4 to obtain mixture 4;

[0027] Mixing the mixture 4 with the pigment and the filler uniformly, referred to as mixing 5, and grinding to obtain a mixture 5 having a fineness of no more than 10 μm;

[0028] The aqueous acrylic emulsion and the aqueous polyurethane dispersion are uniformly mixed, which is referred to as Mixing 6, to obtain Mixing 6;

[0029] The mixture 6 and the mixture 5 are uniformly mixed, which is recorded as mixture 7, to obtain mixture 7;

[0030] The mixture 7 is uniformly mixed with the wetting agent and the anti-flash rust agent, which is recorded as mixture 8 to obtain mixture 8. The viscosity of the mixture 8 is adjusted to 80 ku to 90 ku using the thickener to obtain the one-component self-drying water-based anti-corrosion coating.

[0031] In one embodiment provided in the present application, the mixing time of the mixing 1 is 10 min to 15 min, and the stirring rate of the mixing 1 is 600 r / min to 800 r / min.

[0032] In one embodiment provided in the present application, the mixing time of the mixing 2 is 20 min to 30 min, and the stirring rate of the mixing 2 is 600 r / min to 800 r / min.

[0033] In one embodiment provided in the present application, the mixing time of the mixing 3 is 10 min to 15 min, and the stirring rate of the mixing 3 is 600 r / min to 800 r / min.

[0034] In one embodiment provided in the present application, the mixing time of the mixing 4 is 5 min to 10 min, and the stirring rate of the mixing 4 is 600 r / min to 800 r / min.

[0035] In one embodiment provided in the present application, the mixing time of the mixing 5 is 20 min to 30 min; the mixing rate of the mixing 5 is 1000 r / min to 1200 r / min.

[0036] In one embodiment provided in the present application, the mixing time of the mixing 6 is 10 min to 15 min, and the mixing rate of the mixing 6 is 500 r / min to 700 r / min.

[0037] In one embodiment provided in the present application, the mixing time of the mixing 7 is 20 min to 30 min, and the mixing rate of the mixing 7 is 800 r / min to 1000 r / min.

[0038] In one embodiment provided in the present application, the mixing time of the mixing 8 is 20 min to 30 min, and the mixing rate of the mixing 8 is 800 r / min to 1000 r / min.

[0039] The one-component self-drying water-based paint currently used has poor anti-corrosion and anti-rust functions, and its salt spray resistance is usually less than 240 hours. It also has poor construction compatibility, such as being difficult to match with a two-component water-based polyurethane system (which may cause problems such as bottom biting, affecting the performance of the paint film). The two-component water-based epoxy system has its own drawbacks, such as a short application period after mixing and poor weather resistance.

[0040] The present application overcomes the shortcomings of the prior art, and by mixing the components and making full use of the advantages of each component, the effect of one plus one being greater than two is achieved, so that the density and cross-linking density of the paint film are greatly improved during the film-forming process of the system, thereby improving the various properties of the paint film. The technical solution provided by the present application can provide a one-component self-drying water-based coating with low VOC content, rapid drying and excellent salt spray resistance. It can resist salt spray for up to 720 hours, has excellent adhesion to most substrates, good chemical resistance, weather resistance of up to 500 hours, excellent initial water resistance (water resistance for 24 hours after drying for 2 hours), and can be dried by baking at 80°C for 30 minutes. It is very suitable for bottom-to-top integrated products, especially for use with a two-component waterborne polyurethane system.

[0041] The present application provides a one-component, self-drying, water-based anti-corrosion paint that can be used as both a base and a surface, and has excellent weather resistance and anti-corrosion and anti-rust functions. It has a low VOC content, high hardness, excellent adhesion, good salt spray resistance, excellent weather resistance, and excellent construction compatibility (it can be used with a variety of products such as two-component polyurethane topcoat, acrylic topcoat, alkyd topcoat, epoxy topcoat, etc.), and is particularly suitable for use as various base and surface-in-one products.

[0042] The synergistic effect of the components of this application greatly improves the hardness and density of the paint film of the system, thereby ensuring good physical and chemical properties. The water-based acrylic emulsion in the system can ensure the excellent weather resistance, quick drying, initial water resistance, etc. of the system. It also has excellent weather resistance and leveling properties, and can increase the adhesion between coatings, thereby ensuring the excellent workability of the system. It can be sprayed, brushed, poured, rolled, electrostatically, and high-pressure airless sprayed. Various constructions, while ensuring that the system can be used in conjunction with a variety of different topcoats (two-component polyurethane topcoat, acrylic topcoat, alkyd topcoat, epoxy topcoat).

[0043] Compared with the prior art, this application has the following advantages:

[0044] 1. Excellent salt spray resistance and weather resistance. As a water-based one-component self-drying paint, the product in this application has both excellent salt spray resistance and weather resistance, which fills the gap that water-based one-component self-drying paint cannot take into account.

[0045] 2. Excellent adhesion and compatibility. This product has excellent adhesion to most common substrates (such as cast iron, various steel plates, machined surfaces, various aluminum parts, various stainless steel alloy parts, galvanized parts, etc.), and has strong compatibility, that is, it can be used with two-component polyurethane, acrylic, polyurethane, alkyd, epoxy and other systems, which greatly expands the application field of the product.

[0046] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be invented and obtained by the schemes described in the description. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application are described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0048] In the examples and comparative examples of the present application, the water-based acrylic emulsion is Wanhua Chemical Wantipro 0620; the water-based polyurethane dispersion is Wanhua Chemical Wantipro 0347; the alkyd resin is Tongde Chemical's epoxy acrylic modified self-emulsifying alkyd resin dispersion resin 3AK24B; and the amino resin is Allnex's hexamethoxymethyl melamine resin CYMEL 303LF.

[0049] The pH adjuster is dimethylethanolamine; the co-solvent is dipropylene glycol dimethyl ether DMM; the defoamer is a mixture of Tego843 from Digo and BYK011 from BYK Chemical in a weight ratio of 1:3; the dispersant is a mixture of Verapon B110 and PORON NC in a weight ratio of 2:1; the wetting agent is Surfynol AD01 from Air Chemical; the thickener is a mixture of Rohm and Haas RM-12W and Hemmings Rheolate 299 in a weight ratio of 1:1; the flash rust inhibitor is a mixture of Hemmings ED617F and Shanghai Pengpan 142DA in a weight ratio of 1:1; the pigment is Longmang Titanium Dioxide LR-996 titanium dioxide; the filler is a mixture of precipitated barium sulfate passing through a 1500 mesh sieve, talc passing through a 1500 mesh sieve, and aluminum tripolyphosphate in a weight ratio of 1:1:1.

[0050] The preparation methods of the embodiments and comparative examples are as follows:

[0051] The alkyd resin, the cosolvent and the pH adjuster are uniformly mixed, which is referred to as Mixing 1 to obtain Mixing 1; the mixing time of Mixing 1 is 10 minutes, and the stirring rate of Mixing 1 is 700 r / min;

[0052] The mixture 1 and the amino resin are uniformly mixed, which is recorded as mixture 2 to obtain mixture 2; the mixing time of the mixture 2 is 20 minutes, and the stirring rate of the mixture 2 is 700 r / min;

[0053] Mixing the mixture 2 and the deionized water uniformly, recorded as mixture 3, to obtain mixture 3;

[0054] Optionally, the mixing time of the mixing 3 is 10 min, and the stirring rate of the mixing 3 is 700 r / min;

[0055] The mixture 3 is uniformly mixed with the dispersant and the defoamer, which is recorded as mixture 4 to obtain mixture 4;

[0056] The mixing time of the mixing 4 is 5 min, and the stirring rate of the mixing 4 is 700 r / min;

[0057] Mixing the mixture 4 with the pigment and the filler uniformly, referred to as mixing 5, and grinding to obtain a mixture 5 having a fineness of no more than 10 μm;

[0058] The mixing time of the mixing 5 is 20 min; the mixing rate of the mixing 5 is 1000 r / min;

[0059] The aqueous acrylic emulsion and the aqueous polyurethane dispersion are uniformly mixed, which is recorded as Mixing 6 to obtain Mixing 6; the mixing time of Mixing 6 is 10 minutes, and the mixing rate of Mixing 6 is 600 r / min;

[0060] The mixture 6 and the mixture 5 are uniformly mixed, which is recorded as mixture 7, to obtain mixture 7;

[0061] The mixing time of the mixing 7 is 20 min, and the mixing rate of the mixing 7 is 900 r / min;

[0062] The mixture 7 is evenly mixed with the wetting agent and the anti-flash rust agent, recorded as mixture 8, to obtain mixture 8, and the viscosity of the mixture 8 is adjusted to 80 to 90 ku using the thickener to obtain the one-component self-drying water-based anti-corrosion coating; the mixing time of the mixture 8 is 20 min, and the mixing rate of the mixture 8 is 900 r / min.

[0063] The amounts of raw materials used in the examples and comparative examples are detailed in Table 1.

[0064] Table 1: Raw material dosage of Examples and Comparative Examples

[0065]

[0066] The performance comparison between the examples of the present application and the comparative examples is shown in Table 2:

[0067] Table 2: Performance comparison of examples and comparative examples

[0068]

Claims

1. A one-component self-drying water-based anticorrosive coating, characterized in that: The one-component self-drying water-based anticorrosive coating comprises, by weight: 30 to 40 parts of water-based acrylic emulsion, 8 to 12 parts of alkyd resin, 4 to 6 parts of water-based polyurethane dispersion, 4 to 6 parts of amino resin, 1.5 to 2 parts of pH regulator, 5 to 10 parts of deionized water, 2 to 4 parts of cosolvent, 0.3 to 0.5 parts of wetting agent, 0.3 to 0.5 parts of dispersant, 0.2 to 0.3 parts of defoamer, 2 to 20 parts of pigment, 10 to 25 parts of filler, 0.5 to 1 parts of anti-flash rust agent and 0.5 to 1 parts of thickener; The aqueous acrylic emulsion is a multiphase self-crosslinking anionic acrylic acid-styrene copolymer emulsion; The aqueous polyurethane dispersion is a polycarbonate polyurethane dispersion; The alkyd resin is an epoxy acrylic modified alkyd resin; The amino resin is hexamethoxymethyl melamine resin.

2. The one-component self-drying water-based anticorrosive coating according to claim 1, characterized in that: The pH regulator is selected from any one or more of dimethylethanolamine, inorganic silanol and 2-amino-2-methyl-1-propanol; The co-solvent is selected from any one or more of dipropylene glycol dimethyl ether DMM, dipropylene glycol methyl ether DPM and propylene glycol methyl ether propionate PMP.

3. The one-component self-drying water-based anticorrosive coating according to claim 1, characterized in that: The defoaming agent is selected from any one or more of Tego843, BYK011, DF-208 of Shanghai Zhongyi Chemical, and Evonik Foamex812; The dispersant is selected from any one or more of Shanghai Yuanhe Chemical Verapon B110, Shanghai Zhongyi Chemical DP-610, Evonik GA-100 and Arkema Coadis 790.

4. The one-component self-drying water-based anticorrosive coating according to claim 3, characterized in that: The defoamer is a mixture of Tego 843 and BYK 011 in a weight ratio of 1:

3.

5. The one-component self-drying water-based anticorrosive coating according to any one of claims 1 to 4, characterized in that: The wetting agent is selected from any one or more of Surfynol AD01 of Air Chemistry, Surfynol 104 of Evonik, WA-541B of Shanghai Zhongyi Chemical, and BYK-P104 of BYK Chemical; The thickener is selected from any one or more of Rohm and Haas RM-12W, Hemmings Rheolate 299, Shanghai Zhongyi Chemical's CX-380, Arkema's 53L and Evonik 3010.

6. The one-component self-drying water-based anticorrosive coating according to claim 5, characterized in that: The thickener is a mixture of Rohm and Haas RM-12W and Hemmings Rheolate 299 in a weight ratio of 1:

1.

7. The one-component self-drying water-based anticorrosive coating according to any one of claims 1 to 4, characterized in that: The flash rust preventer is selected from any one or more of Hemmings ED617F, Shanghai Pengpan 142DA, Beijing Zhitu Chemical ZT706 and Shanghai Tianyu Chemical ED-617F.

8. The one-component self-drying water-based anticorrosive coating according to claim 7, characterized in that: The anti-flash rust agent is a mixture of Hemmings ED617F and Shanghai Pengpan 142DA in a weight ratio of 1:

1.

9. The one-component self-drying water-based anticorrosive coating according to any one of claims 1 to 4, characterized in that: The pigment is selected from titanium dioxide; The filler is selected from any one or more of barium sulfate, talc and aluminum tripolyphosphate.

10. The one-component self-drying water-based anticorrosive coating according to claim 9, characterized in that: The titanium dioxide is selected from Lomon Titanium Dioxide LR-996.

11. The one-component self-drying water-based anticorrosive coating according to claim 9, characterized in that: The barium sulfate is precipitated barium sulfate that has passed a 1500-mesh sieve, and the talc powder is talc powder that has passed a 1500-mesh sieve.

12. The one-component self-drying water-based anticorrosive coating according to claim 9, characterized in that: The filler is a mixture of barium sulfate, talcum powder and aluminum tripolyphosphate in a weight ratio of 1:1:

1.

13. The method for preparing the one-component self-drying water-based anticorrosive coating according to any one of claims 1 to 12, characterized in that: The steps include: The alkyd resin, the cosolvent and the pH adjuster are uniformly mixed, which is referred to as Mixing 1 to obtain Mixing 1; The mixture 1 and the amino resin are uniformly mixed, which is referred to as mixture 2, to obtain mixture 2; Mixing the mixture 2 and the deionized water uniformly, recorded as mixture 3, to obtain mixture 3; The mixture 3 is uniformly mixed with the dispersant and the defoamer, which is recorded as mixture 4 to obtain mixture 4; Mixing the mixture 4 with the pigment and the filler uniformly, referred to as mixing 5, and grinding to obtain a mixture 5 having a fineness of no more than 10 μm; The aqueous acrylic emulsion and the aqueous polyurethane dispersion are uniformly mixed, which is referred to as Mixing 6, to obtain Mixing 6; The mixture 6 and the mixture 5 are uniformly mixed, which is recorded as mixture 7, to obtain mixture 7; The mixture 7 is uniformly mixed with the wetting agent and the anti-flash rust agent, which is recorded as mixture 8 to obtain mixture 8. The viscosity of the mixture 8 is adjusted to 80 ku to 90 ku using the thickener to obtain the one-component self-drying water-based anti-corrosion coating.

14. The preparation method according to claim 13, wherein: The mixing time of the mixing 1 is 10 min to 15 min, and the stirring rate of the mixing 1 is 600 r / min to 800 r / min; The mixing time of the mixing 2 is 20 min to 30 min, and the stirring rate of the mixing 2 is 600 r / min to 800 r / min; The mixing time of the mixing 3 is 10 min to 15 min, and the stirring rate of the mixing 3 is 600 r / min to 800 r / min; The mixing time of the mixing 4 is 5 min to 10 min, and the stirring rate of the mixing 4 is 600 r / min to 800 r / min; The mixing time of the mixing 5 is 20 min to 30 min; the mixing rate of the mixing 5 is 1000 r / min to 1200 r / min; The mixing time of the mixing 6 is 10 min to 15 min, and the mixing rate of the mixing 6 is 500 r / min to 700 r / min; The mixing time of the mixing 7 is 20 min to 30 min, and the mixing speed of the mixing 7 is 800 r / min to 1000 r / min; The mixing time of the mixing process 8 is 20 min to 30 min, and the mixing speed of the mixing process 8 is 800 r / min to 1000 r / min.

Citation Information

Patent Citations

  • Epoxy acrylate modified waterborne alkyd resin and preparation method and application thereof

    CN104086712A

  • Single component air-drying water-based rust inhibiting primer with curtaining capacity and used for electrical equipment housing as well as preparation method of primer

    CN104356795A

  • Water-based self-crosslinking acrylic self-drying paint and preparation method thereof

    CN109627858A

  • Water-based golden oil having high salt spray resistance and used for zinc alloy nickel-plated wire drawing materials and preparation method of water-based golden oil

    CN110591474A